Re-conceptualising education policy trajectories in a globalised world: lessons from a multi-level comparison of accountability in France and Quebec. Issue 4 (2nd October 2021) - Maroy, Christian; Pons, Xavier
ABSTRACT: This article aims to show the value of the concept of policy trajectory to compare, from a long-term perspective, the transformations of education policies in the context of globalisation. After discussing the scope and limitations of the analyses of the concept in the literature – descriptive, sequential, metaphorical and building on the works of Stephen Ball –, we propose, our own conceptualisation. This regards policy trajectory as a double shift in time and space and understood as the result of different processes of path dependency, translation and bricolage. The forms of this trajectory depend on the educational orders at work at different levels of school systems, and not only at the global level. To illustrate this approach, we draw on a study which compared performance-based accountability policies in France and Quebec. Despite some challenges, this approach has the merit of proposing a fruitful theoretical framework for studying and comparing policy implementation.